Wastewater Management Policies for Nuclear Power Plants and its Implementation in China - Ding, Xiaowen; Jiang, Guihong; Hou, Baodeng; Xue, Ying (Journal of Environmental Accounting and Management, 2026)
To deal with the global climate change and energy shortage, nuclear power has been widely used all over the world for its low carbon emission and economic cost. Nowadays, hundreds of nuclear power plants have been constructed in many countries. However, the operation of them discharged radioactive effluents and non-radioactive wastewater into nearby water bodies, which makes wastewater management policies for such plants crucial. The objective of this study is to summarize laws, regulations and technical standards of major countries with nuclear power plants, and advance wastewater management of nuclear power plants for China. This article summarized the laws, regulations and technical standards of wastewater management for the plants in major countries with nuclear power plants as well as International Atomic Energy Agency. The management in China, including management process, authorities, public participation as well as emergency system, was also proposed considering that plenty of coastal nuclear power plants had been built, and several inland ones were taken into account. Furthermore, case study was developed for Tianwan nuclear power plant which lied in East Coast of China and had been operated for ten years. The results may provide the managers of nuclear power plants around the world a policy reference and a decision support in the field of wastewater management.